Fusicoccin Synthesis by Intramolecular [4+4] Photocycloaddition of 2-Pyridones: Stereocontrol of the Cycloaddition and Elaboration of the Pentacyclic Product - McGee, Kevin F., Jr.; Al-Tel, Taleb H.; Sieburth, Scott Mc N. (Synthesis, 2001)
Intramolecular photocycloaddition of a three-carbon tethered pyrindinone–pyridone system yields the 5-8-5 ring system of the fusicoccin/ophiobolin/ceroplastol families. The stereoselectivity of the cycloaddition was found to be dependent on nitrogen substitution; N-methylation led to exclusively trans products while an absence of nitrogen substitution resulted in solvent-dependent stereoselectivity. Solvent and concentration effects for this cycloaddition were consistent with a hydrogen-bonded dimer that enforces a pro-cis conformation in nonpolar solvents and at higher concentrations. The cis-isomer, a fusicoccin synthesis intermediate, underwent a Cope rearrangement at ambient temperature but could be trapped efficiently as the mono epoxide, yielding a product with six new stereogenic centers. A four-step transformation of an amide carbonyl to a methyl group was achieved using a carbamoyl group to activate the amide for cleavage.
Keywords: fusicoccin; higher-order cycloadditions; photochemistry; stereoselectivity; solvent effects